Developing a best practice guide for integrating spiritual care interventions in chronic pain therapy: a qualitative Delphi study - Perrin, Joël; Hasenfratz, Karin; Peng-Keller, Simon; Rufer, Michael; Naef, Rahel (Frontiers in Pain Research, 2025)
Chronic pain patients (CPPs) often face complex, multifactorial challenges, with many reporting that their pain management lacks comprehensiveness. Spiritual care has emerged as a potential resource in addressing the diverse needs of CPPs, but remains underutilized due to healthcare professionals' (HCPs) uncertainty about how to integrate it into clinical practice. This study aimed to develop a best practice guide for integrating spiritual care into chronic pain therapy using a qualitative Delphi study. Three rounds of data collection, involving a panel of CPPs and HCPs with expertise in chronic pain from various disciplines, were conducted. Participants shared their experiences and suggestions for addressing spiritual aspects in pain therapy. The process led to the formulation of a consensus-based best practice guide, outlining practical strategies for HCPs to engage with spiritual care in a way that is respectful and sensitive to individual patient needs. Results indicated that incorporating spiritual care in chronic pain therapy can enhance therapeutic relationships, foster more meaningful patient interactions, and provide additional coping mechanisms. The guide was rated as clinically applicable, and offers a structured yet flexible framework for integrating spiritual care into multimodal pain treatment and is expected to improve patient outcomes by addressing existential aspects of chronic pain.